MEXICO INTERNATIONAL BUSINESS OVERVIEW - Rahmaniar; Khairil Anwar; Muhammad Ade Hendarso; Aisah; Khadijah Vanny (RADJA PUBLIKA, 2023)
Mexican international business involves all economic transactions related to international trade and foreign investment. Mexico has a fairly strong business relationship with the US, of which the US is its largest trading partner. The main business owned by Mexico comes from the wholesale and retail trade sector. Mexico's international business includes both export and import. Mexico is a major producer and exporter of crude oil, electronics and automobiles. Plus, Mexico tooimporting raw materials and machinery for the purpose of producing goods to be sold domestically. Foreign investment in Mexico is sourced from various sectors, including manufacturing, tourism, and financial services. Mexico offers several incentives to attract foreign investors, such as lower taxes and access to the North American market. However, Mexican international business also has its own challenges, such as corruption and crime related to the drug trade. Therefore, through planning that is quite long and creative and innovative ideas are needed to assist the City Government in dealing with these challenges.